Method for preparing electrostatic spinning flexible piezoresistive sensor with micro-cone structure without template

By using thermoplastic polyurethane/carboxylated carbon nanotubes/MXene electrospinning technology in flexible piezoresistive sensors to form nano-microcone structures and high-porosity conductive networks, the limitations of existing sensors in sensitivity, detection range and thickness are solved, and high-performance, low-cost human motion monitoring applications are achieved.

CN120592035APending Publication Date: 2025-09-05KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510721267.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

Existing flexible piezoresistive sensors have limitations in sensitivity, detection range and thickness, and are particularly ineffective in human motion monitoring. They also have high production costs and complex processes.

Method used

Using thermoplastic polyurethane/carboxylated carbon nanotubes/MXene electrospinning technology, the nano-microcone structure is self-aggregated on the film surface by regulating the electrospinning parameters, and a high-porosity conductive network is formed through the bonding effect of MXene nanosheets and thermoplastic polyurethane.

Benefits of technology

A highly sensitive, wide detection range, ultra-thin flexible piezoresistive sensor with short response time and good cycling stability was achieved, simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120592035A_ABST
    Figure CN120592035A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flexible piezoresistive sensors, in particular to a preparation method of an electrostatic spinning flexible piezoresistive sensor for preparing a micro-cone structure without a template, according to the preparation method, electrostatic spinning parameters are regulated and controlled, and nano micro-cone structures which are uniformly distributed are formed on the surface of a carboxylated carbon nanotube / thermoplastic polyurethane electrostatic spinning film through self-aggregation. In the step S7, a G21 needle, 7.6 KV voltage and a material pushing rate of 0.0030 mm / s are adopted, so that the spinning solution forms beaded fibers under the action of an electric field, nanoparticles are induced to gather on the surfaces of the fibers through the synergistic effect of solvent volatilization and fiber stretching, and finally a highly-ordered conical microstructure is formed. The prepared piezoresistive flexible sensor is high in sensitivity, has a micro-cone microstructure, is low in detection limit, short in response time, wide in strain detection range, good in cycling stability, simple in preparation process and low in cost, and has application potential in the fields of human motion monitoring, health monitoring management and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flexible piezoresistive sensors, and in particular to a method for preparing an electrostatic spinning flexible piezoresistive sensor with a micro-cone structure without a template. Background Art

[0002] Flexible pressure sensors are sensors that can sense and respond to changes in external pressure. They are flexible and stretchable, making them suitable for use on a variety of complex surfaces and in dynamic environments. They can be attached, implanted, or installed on surfaces or structures to detect pressure. Flexible pressure sensors play a vital role in various fields, including engineering, sports, and medicine, particularly in medicine and sports. In recent years, the continuous innovation and development of flexible pressure sensors has driven the development of human health monitoring and electronic equipment towards greater intelligence, convenience, and comfort, bringing positive impacts to scientific and technological progress and human life.

[0003] However, current flexible sensor devices are limited by sensitivity, detection range, and thickness, and are limited in the detection of cyclic human motion. For example, patent number CN222419323U discloses a piezoresistive sensor with an isolation configuration. By combining an electrode layer with a microstructure electrode having a high and low distribution trapezoidal protrusion structure, the sensitivity and accuracy of the piezoresistive sensor are effectively improved. However, its manufacturing process requires template etching and the use of magnetron sputtering technology, which results in a high manufacturing cost and a complex process flow. At the same time, due to size limitations, the detectable range of the corresponding pressure is small and the thickness is large, and defects still exist to a certain extent. Therefore, the development of flexible piezoresistive sensors with high sensitivity, wide detection range and ultra-thinness is of great significance for monitoring large-scale human body movements and continuous repetitive movements. Summary of the Invention

[0004] The present invention aims to provide a method for preparing a thermoplastic polyurethane / carboxylated carbon nanotube / MXene electrospun flexible piezoresistive sensor. The method involves self-aggregating a uniformly distributed nano-microconical structure on the surface of a carboxylated carbon nanotube / thermoplastic polyurethane electrospun film, and then ultrasonically bonding the MXene to the thermoplastic polyurethane. The resulting piezoresistive flexible sensor exhibits high sensitivity, a microconical microstructure, a low detection limit, a short response time, a wide strain detection range, and excellent cyclic stability. Furthermore, the method is simple and low-cost, and has potential applications in areas such as human motion monitoring and health monitoring and management.

[0005] The present invention adjusts the electrospinning parameters (such as needle type, voltage, pushing rate, etc.) to form uniformly distributed nano-micro cone structures (such as attached nano-cones) on the surface of the carboxylated carbon nanotube / thermoplastic polyurethane electrospinning film. Figure 4(a)(b)). In step S7, a G21 needle, 7.6 kV voltage, and a feed rate of 0.0030 mm / s were used to form beaded fibers from the spinning solution under the action of the electric field. The synergistic effect of solvent evaporation and fiber stretching induced the nanoparticles to aggregate on the fiber surface, ultimately forming a highly ordered conical microstructure. This microconical structure has the following advantages:

[0006] 1. The tapered tip can significantly increase the local electric field strength and improve the contact area change rate under pressure, thereby enhancing sensitivity;

[0007] 2. The combination of microcones and the high porosity of the electrospun layer can synergistically expand the effective strain range of the sensor;

[0008] 3. MXene nanosheets are bonded to the microcone surface through a subsequent impregnation process (step S9), further optimizing the conductive network and reducing the contact resistance.

[0009] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0010] A method for preparing an electrospinning flexible piezoresistive sensor with a micro-cone structure without a template, comprising the following steps:

[0011] S1: Mix N,N-dimethylformamide and tetrahydrofuran, and stir until fully dispersed to obtain a mixed solvent;

[0012] S2: dissolving hydrogen fluoride in a hydrochloric acid solution having a concentration of 9 mol / L to form a hydrogen fluoride-hydrochloric acid mixture;

[0013] S3: Add MAX precursor to the mixture of S2, stir magnetically in a 45°C water bath for 36 hours, and wash to pH = 6 to obtain MXene nanosheets;

[0014] S4: dispersing the MXene nanosheets obtained in step S3 in anhydrous ethanol to prepare a MXene / ethanol dispersion;

[0015] S5: adding the carboxylated carbon nanotubes to the mixed solvent of step S1 at a mass ratio of 1:(800-1000), and performing ultrasonic treatment at a power of 12% for 10-40 minutes to obtain a carboxylated carbon nanotube dispersion;

[0016] S6: adding thermoplastic polyurethane to the dispersion of step S5 at a mass ratio of 1:(8-10), stirring at 160 rpm / min at room temperature for 8 hours to form a spinning solution;

[0017] S7: Inject the spinning solution from step S6 into a 10 ml syringe with a G21 needle, control the screw position to 35 mm, the voltage to 7.6 kV, and the pushing rate to 0.0030 mm / s, and electrospin for 1-2 hours at a temperature of 20° C. and a humidity of 60% RH to form a fiber film with a beaded structure;

[0018] S8: placing the film from step S7 in a constant temperature and humidity chamber at 5% RH and 25° C., heating the chamber at a rate of 5° C. / min to 40° C. and maintaining the temperature for 2 hours to obtain a carboxylated carbon nanotube / thermoplastic polyurethane film having a micro-cone structure;

[0019] S9: Immerse the film from step S8 in the MXene / ethanol dispersion from step S4 for 1 hour, and air-dry to obtain a carboxylated carbon nanotube / thermoplastic polyurethane / MXene composite film.

[0020] Furthermore, in step S2, 0.4 g of hydrogen fluoride is dissolved in 5 ml of 9 mol.L-1 hydrochloric acid solution to obtain a mixed dispersion of hydrogen fluoride and hydrochloric acid.

[0021] Furthermore, in step S3, 0.003 g of MAX precursor was added to the mixed dispersion of hydrogen fluoride and hydrochloric acid, and the resulting mixture was magnetically stirred in a 45° C. water bath for 36 h, and washed with deionized water until the pH of the resulting supernatant was approximately 6, thereby obtaining MXene nanosheets.

[0022] Furthermore, in step S5, the mass ratio of the carboxylated carbon nanotubes to the mixed solvent is 1:1000, and the ultrasonic treatment time is 40 minutes.

[0023] Furthermore, in step S6, the mass ratio of the thermoplastic polyurethane to the mixed solvent is 1:10.

[0024] Furthermore, the electrospinning time in step S7 is 2 hours.

[0025] Furthermore, in step S9, the MXene nanosheets are combined with the thermoplastic polyurethane through bonding.

[0026] Beneficial effects of the present invention:

[0027] The present invention utilizes specific electrospinning process parameters rather than traditional template transfer and micro-nanofabrication methods to achieve in situ self-assembly of highly uniform nano-cone structures on the surface of carboxylated carbon nanotube / thermoplastic polyurethane composite nanofibers. By selecting the appropriate solvent ratio, ultrasonic dispersion time, and key electrospinning parameters, the solution forms special beaded fibers under the action of an electric field, and the nanoparticles are localized and aggregated on the fiber surface, ultimately inducing an ordered and densely distributed nano-cone microstructure. Such microstructures can undergo significant deformation under minimal pressure, resulting in a dramatic change in the piezoresistive signal and significantly improving the sensitivity of the sensor. Furthermore, the high porosity of the electrospun membrane itself greatly expands the deformable range, achieving a wide pressure response range. Compared to traditional microstructure layers that rely on template etching and transfer, the present invention offers higher integration, a shorter process chain, lower costs, and greater controllability in preparation, significantly promoting the engineering and mass production of nanostructured flexible sensors.

[0028] The material system of the present invention is a multi-component synergistic construction of thermoplastic polyurethane, carboxylated carbon nanotubes, and MXene nanosheets, resulting in highly optimized structural and interfacial properties. Thermoplastic polyurethane, the primary framework material, possesses excellent flexibility and resilience, maintaining overall integrity and morphological stability during repeated compression and deformation, providing the mechanical foundation for reliable microcone deformation. The carboxylated carbon nanotubes not only serve as an efficient conductive framework, but their surface carboxyl functional groups significantly enhance their dispersibility in N,N-dimethylformamide / tetrahydrofuran, preventing aggregation and accumulation, thereby ensuring uniform formation of electrospun nanofibers and their surface microcone structures. These dispersed nanotubes form three-dimensional interconnected conductive pathways within the fiber network, enabling sensitive conversion of microstructural deformation into electrical signals. After film formation, the MXene nanosheets are further impregnated, leveraging hydrogen bonding or van der Waals interactions between the abundant surface functional groups and polyurethane molecules to achieve effective MXene adhesion to the microcones and fiber surfaces. This further optimizes the conductive network at the composite interface, reduces electrical contact impedance, and improves the overall piezoresistance change rate. The multi-component synergistic material system not only ensures the high flexibility and toughness of the film, and the stability of its morphology and performance during cyclic compression, but also optimizes the triple path of microstructure-interface-conductivity, providing a solid material foundation for high-performance flexible piezoresistive sensors.

[0029] This invention details the optimal process window for each step, from material dispersion and solution proportioning to electrospinning. By scientifically controlling the solvent ratio, ultrasonic conditions, material proportioning, ambient temperature and humidity, and multiple electrospinning parameters, it achieves adjustable morphology and predictable performance of micro-conical nanofiber membranes. Carboxylated carbon nanotubes are dispersed at an appropriate concentration and with sufficient ultrasonication before electrospinning, enhancing the conductivity of the mixed solution while effectively preventing excessive aggregation that compromises spinning continuity and microstructure formation. The optimal matching of spinning voltage and feed rate enables rapid stretching of the nanosolution under a high electric field. Simultaneously, surface nanoparticle aggregation and solvent evaporation synergistically generate a uniform conical microstructure. Post-film formation, a temperature and humidity gradient treatment further solidifies the microstructure morphology, ensuring consistency across batches during mass production. After spinning, the film is then impregnated with MXene to strengthen the conductive interface, ensuring that each layer of material can maximize its functionality. This significantly improves product yield and stability while also enabling flexible adjustment of detection sensitivity and response range for different application scenarios, laying a solid foundation for large-scale industrialization and high-end customized applications.

[0030] The present invention realizes a multi-level response piezoresistive sensing mechanism through the collaborative construction of a beaded nanofiber network and surface microcones. When a small pressure is applied, the surface nanocones first undergo elastic deformation, rapidly increasing the actual contact area between the upper and lower conductive layers, and the piezoresistive sensing signal is significantly enhanced; as the pressure increases, the microcone structure gradually plastically deforms, and the high-porosity support of the fiber layer continues to release deformation space, ensuring that the sensor has good sensitivity and linear response throughout the entire process from low pressure to high pressure. The ultra-thin, flexible and porous nature of the material ensures that the device can be highly adaptable to any curved surface such as skin, joints and other complex parts without affecting comfort and breathability, and is suitable for large-scale repeated bending or small movement monitoring, meeting the needs of high-end flexible wearable scenarios such as human sports health and electronic skin. The combination and synergy of the triple structure greatly enhances the signal amplitude, response speed and cycle life of the sensor, while avoiding the many limitations of traditional thick film or rigid microstructure devices due to large thickness, structural fatigue or signal saturation, and promoting the miniaturization and intelligentization of flexible electronics and intelligent sensing systems.

[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 Schematic diagram of the electrospun film fiber described in the present invention.

[0034] Figure 2 Schematic diagram of the sensing mechanism of the flexible piezoresistive sensor prepared in Example 1 of the present invention.

[0035] Figure 3 The figure is a flow chart of the preparation of the electrospinning film described in the present invention.

[0036] Figure 4 (a) is a surface SEM image of the carboxylated carbon nanotubes / thermoplastic polyurethane / MXene described in the present invention, and (b) is a SEM image of the conical microstructure on the surface of the carboxylated carbon nanotubes / thermoplastic polyurethane / MXene described in the present invention.

[0037] Figure 5 It is the minimum pressure detection limit of the carboxylated carbon nanotube / thermoplastic polyurethane / MXene electrospinning film described in the present invention.

[0038] Figure 6 This is a sensitivity diagram of the flexible piezoresistive sensor prepared in Example 1 of the present invention.

[0039] Figure 7 This is the response speed of the flexible piezoresistive sensor prepared in Example 1 of the present invention.

[0040] Figure 8 Comparison of the sensitivity of TPU / MWCNTs-COOH and TPU / MWCNTs-COOH / MXene.

[0041] Figure 9 This is a schematic diagram of the cycle of the flexible piezoresistive sensor prepared in Example 1 of the present invention under a pressure of 5 kPa for 1400 seconds.

[0042] Figure 10 This is an SEM image of a flexible piezoresistive sensor prepared using parameters other than those in Example 1.

[0043] In the accompanying drawings, the components represented by the reference numerals are as follows:

[0044] 1. PI tape, 2. Copper foil, 3. Carboxylated carbon nanotube / thermoplastic polyurethane / MXene electrospun film, 4. Beaded structure of electrospun fibers, 5. Schematic diagram of bonding of electrospun fibers, 6. Two-dimensional model of nano-microcone structure, 7. Carboxylated carbon nanotubes, 8. Beaker, 9. N,N-dimethylformamide / tetrahydrofuran dispersion, carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran / thermoplastic polyurethane dispersion, 10. Magnetic stirrer, 11. Ultrasonic crushing Instrument, 12. Thermoplastic polyurethane, 13. Carboxylated carbon nanotubes / N,N-dimethylformamide / tetrahydrofuran dispersion, 14. Electrospinning, 15. Carboxylated carbon nanotubes / N,N-dimethylformamide / tetrahydrofuran / thermoplastic polyurethane electrospinning film, 16. Constant temperature and humidity chamber, 17. MXene nanosheets, 18. Anhydrous ethanol, 19. Rotor, 20. MXene / anhydrous ethanol mixed dispersion solution, 21. Carboxylated carbon nanotubes / thermoplastic polyurethane electrospinning film. DETAILED DESCRIPTION

[0045] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0046] Example 1

[0047] In this embodiment, the verification is further performed using mass units, which specifically includes the following steps:

[0048] S1: Add 6 g of N,N-dimethylformamide and 6 g of tetrahydrofuran into a beaker, and stir and mix them evenly at room temperature to obtain an N,N-dimethylformamide / tetrahydrofuran mixed solution.

[0049] S2: Dissolve 0.4 g of hydrogen fluoride in 5 ml of 9 mol.L -1 A mixed dispersion of hydrogen fluoride and hydrochloric acid is obtained in the hydrochloric acid solution.

[0050] S3: Add 0.003 g of MAX precursor to the mixed dispersion of hydrogen fluoride and hydrochloric acid in S2, magnetically stir the resulting mixture in a 45°C water bath for 36 h, and wash with deionized water until the pH of the resulting supernatant is approximately 6 to obtain MXene nanosheets.

[0051] S4: 0.3 g of MXene nanosheets prepared in S3 was added to 10 ml of anhydrous ethanol solution to obtain a MXene / anhydrous ethanol mixed dispersion solution.

[0052] S5: Add carboxylated carbon nanotubes in a mass ratio of 1:1000 to the solution obtained in S1 to the N,N-dimethylformamide / tetrahydrofuran mixed solution dispersion in S1, and perform ultrasonic treatment at a power of 12% for 40 minutes to obtain a carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran mixed solution dispersion.

[0053] S6: To the carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran dispersion obtained in S5, thermoplastic polyurethane was added in a mass ratio of 1:10 to the solution obtained in S1, and stirred at 160 rpm / min at room temperature for 8 hours to obtain a black carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran / thermoplastic polyurethane dispersion.

[0054] S7: Pour the carboxylated carbon nanotubes / N,N-dimethylformamide / tetrahydrofuran / thermoplastic polyurethane dispersion in S6 into a 10 ml syringe with a needle model of G21. Control the electrospinning parameters, the screw position is 35 mm, the voltage is 7.6 kV, the pushing rate is 0.0030 mm / s, the temperature is 20 ° C, and the humidity is 60% RH. The electrospinning time is 2 hours.

[0055] S8: The spun film obtained in S7 was placed in a constant temperature and humidity chamber at 5% RH and 25°C, and the temperature was increased to 40°C at a heating rate of 5°C / min and maintained for two hours to obtain a carboxylated carbon nanotube / thermoplastic polyurethane electrospun film with a conical microstructure.

[0056] according to Figure 2 It is known that the carboxylated carbon nanotube / thermoplastic polyurethane electrospinning layer is composed of uniform nanowires, and some conical microstructures produced by the aggregation of nanoparticles appear on its surface. These conical structures can effectively improve the relevant performance of the sensor.

[0057] Example 2

[0058] S1: Add 6 g of N,N-dimethylformamide and 6 g of tetrahydrofuran into a beaker, and stir and mix them evenly at room temperature to obtain an N,N-dimethylformamide / tetrahydrofuran mixed solution.

[0059] S2: Dissolve 0.4 g of hydrogen fluoride in 5 ml of 9 mol.L -1 A mixed dispersion of hydrogen fluoride and hydrochloric acid is obtained in the hydrochloric acid solution.

[0060] S3: Add 0.003 g of MAX precursor to the mixed dispersion of hydrogen fluoride and hydrochloric acid in S2, magnetically stir the resulting mixture in a 45°C water bath for 36 h, and wash with deionized water until the pH of the resulting supernatant is approximately 6 to obtain MXene nanosheets.

[0061] S4: 0.3 g of MXene nanosheets prepared in S3 was added to 10 ml of anhydrous ethanol solution to obtain a MXene / anhydrous ethanol mixed dispersion solution.

[0062] S5: Add carboxylated carbon nanotubes at a mass ratio of 1:800 to the solution obtained in S1 to the N,N-dimethylformamide / tetrahydrofuran mixed solution dispersion in S1, and perform ultrasonic treatment at a power of 12% for 40 minutes to obtain a carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran mixed solution dispersion.

[0063] S6: To the carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran dispersion obtained in S5, thermoplastic polyurethane was added in a mass ratio of 1:8 to the solution obtained in S1, and stirred at 160 rpm / min at room temperature for 8 hours to obtain a black carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran / thermoplastic polyurethane dispersion.

[0064] S7: The carboxylated carbon nanotubes / N,N-dimethylformamide / tetrahydrofuran / thermoplastic polyurethane dispersion in S6 was poured into a 10 ml syringe with a needle model of G21. The electrospinning parameters were controlled, the screw position was 35 mm, the voltage was 7.6 KV, the pushing rate was 0.0030 mm / s, the temperature was 20 ° C, and the humidity was 60% RH. Electrospinning was performed for 1.5 hours to obtain a nano-cone structure.

[0065] S8: The spun film obtained in S7 was placed in a constant temperature and humidity chamber at 5% RH and 25°C, and the temperature was increased to 40°C at a heating rate of 5°C / min and maintained for two hours to obtain a carboxylated carbon nanotube / thermoplastic polyurethane electrospun film with a conical microstructure.

[0066] Example 3

[0067] The only difference between the preparation method and Example 1 is that in step S5, the mass ratio of carboxylated carbon nanotubes to the N,N-dimethylformamide / tetrahydrofuran mixed solution is 1:900; in step S6, the mass ratio of thermoplastic polyurethane to the N,N-dimethylformamide / tetrahydrofuran mixed solution is 1:9; and the electrospinning time in S7 is 1 h.

[0068] Comparative Example 1

[0069] S1: Add 6 g of N,N-dimethylformamide and 6 g of tetrahydrofuran into a beaker, and stir and mix them evenly at room temperature to obtain an N,N-dimethylformamide / tetrahydrofuran mixed solution.

[0070] S2: Dissolve 0.4 g of hydrogen fluoride in 5 ml of 9 mol.L -1A mixed dispersion of hydrogen fluoride and hydrochloric acid is obtained in the hydrochloric acid solution.

[0071] S3: Add 0.003 g of MAX precursor to the mixed dispersion of hydrogen fluoride and hydrochloric acid in S2, magnetically stir the resulting mixture in a 45°C water bath for 36 h, and wash with deionized water until the pH of the resulting supernatant is approximately 6 to obtain MXene nanosheets.

[0072] S4: 0.3 g of MXene nanosheets prepared in S3 was added to 10 ml of anhydrous ethanol solution to obtain a MXene / anhydrous ethanol mixed dispersion solution.

[0073] S5: Add carboxylated carbon nanotubes at a mass ratio of 1:800 to the solution obtained in S1 to the N,N-dimethylformamide / tetrahydrofuran mixed solution dispersion in S1, and perform ultrasonic treatment at a power of 12% for 40 minutes to obtain a carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran mixed solution dispersion.

[0074] S6: To the carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran dispersion obtained in S5, thermoplastic polyurethane was added in a mass ratio of 1:8 to the solution obtained in S1, and stirred at 160 rpm / min at room temperature for 8 hours to obtain a black carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran / thermoplastic polyurethane dispersion.

[0075] S7: The carboxylated carbon nanotube / N,N-dimethylformamide / tetrahydrofuran / thermoplastic polyurethane solution prepared in S6 is evenly coated on sandpaper with a conical microstructure using a glass rod and dried to obtain a carboxylated carbon nanotube / thermoplastic polyurethane film with a conical microstructure.

[0076] S8: The spun film obtained in S7 was placed in a constant temperature and humidity chamber at 5% RH and 25°C, and the temperature was increased to 40°C at a heating rate of 5°C / min and maintained for two hours to obtain a carboxylated carbon nanotube / thermoplastic polyurethane electrospun film with a conical microstructure.

[0077] Comparative Example 2

[0078] The only difference between the preparation method of the flexible resistive pressure sensor described in this comparative example and that in Example 1 is that the carboxylated carbon nanotubes are replaced with carbon nanotubes of the same mass.

[0079] Comparative Example 3

[0080] The only difference between the preparation method of the flexible resistive pressure sensor described in this comparative example and that in Example 1 is that in step S7, the spinning parameters are: the screw position is 30 mm, the voltage is 9.6 KV, the pushing speed is 0.0020 mm / s, the temperature is 25°C, the humidity is 60% RH, and the time is 2 hours.

[0081] Effect Example 1

[0082] The flexible pressure sensors prepared in Examples 1-3 and Comparative Examples 1-3 were tested for their sensing performance. A universal testing machine (ZQ950B) with a resolution of 0.001 N was used to apply a load. A Tonghui LCR impedance meter (TH2830) was used to measure the relative change in resistance, ΔR / R0, where ΔR represents the change in resistance and R0 represents the initial resistance.

[0083] 1. The sensitivity of the pressure sensor is: unit pressure change (kPa / cm 2 ) corresponds to the size of the relative change in resistance (ΔR / R0); the value of sensitivity S is equal to the relationship between the relative change in resistance (ΔR / R0) and the unit pressure change (kPa / cm 2 )The slope of the curve.

[0084] from Figure 5 It can be seen that the working principle of the flexible resistive pressure sensor is: the carboxylated carbon nanotube / thermoplastic polyurethane / MXene spinning film sensor can be simplified into a circuit with a series resistor. Figure 5 The circuit is shown in detail, including the interface resistance (R e ) and the contact resistance between the upper and lower layers (R C When pressure is applied to the sensor, the contact area and conductive path between the upper and lower conductive layers change. Without pressure, the raised surface creates a gap between the sensor's upper and lower layers, resulting in a smaller contact area and conductive path. When less pressure is applied, the sensor's upper and lower layers are compressed and deformed, increasing the contact area and conductive path. When greater pressure is applied, the contact between the upper and lower layers of the compression-deformed sensor becomes more pronounced, and the contact area and conductive path continue to increase. At this point, the pressure gradually reaches the maximum value the sensor can detect. In general, the pressure changes the contact area, thereby altering the conductive path. This results in a significant change in the sensor's overall resistance.

[0085] from Figure 6 It can be seen that the flexible resistive pressure sensor of Example 1 shows a sensitivity S1 = 443.63 KPa when 0-4 KPa. -1 , when 4-99kPa, the sensitivity S2=7.791KPa -1, when the temperature is 99-266KPa, the sensitivity S3=1.574KPa -1 , the three stages have different sensitivities. The present invention better combines high sensitivity and a wide detection range (0-266KPa) through the carboxylated carbon nanotube / thermoplastic polyurethane spinning film with a fiber self-aggregated conical microstructure. In the early stage of force, the conical structure of the sensing layer undergoes a large change, so the sensitivity of this stage is relatively high. As the pressure increases, the change in the conical microstructure gradually becomes smaller, resulting in a decrease in sensitivity. When the conical microstructure is fully compressed, it no longer deforms, so the sensitivity of this stage will gradually decrease.

[0086] From the test results, the sensing performance of Example 1 is the best. First, compared with Examples 2-3, the carboxylated carbon nanotube content in the embodiment is relatively moderate. While maintaining the sensing performance, the morphology of the nanofiber obtained by electrostatic spinning is also not greatly affected. When the carboxylated carbon nanotube is too low, the sensing performance will be limited. However, when it is too high, the carboxylated carbon nanotube easily forms larger agglomeration in the solution, causing the electrostatic spinning carboxylated carbon nanotube / thermoplastic polyurethane film morphology to be affected. Compared with Comparative Example 1, the sensing layer obtained by electrostatic spinning in the embodiment has ultra-thin thickness and ultra-high porosity, and its sensitivity is higher. After using carbon nanotubes as spinning material, Comparative Example 2, due to its poor dispersibility in N, N-dimethylformamide / tetrahydrofuran, easily forms agglomeration in the solution, making it impossible to generate an electrostatic spinning film with a tapered microstructure. Compared with Comparative Example 3, Comparative Example 3 changes the parameters of electrostatic spinning and cannot generate an electrostatic spinning film with a tapered microstructure.

[0087] 2. The response time and recovery time of the flexible resistive pressure sensors prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 were tested. Figure 7It can be seen from the data that the response time of the flexible resistive pressure sensor prepared in Example 1 is 40ms and the recovery time is 45ms. Due to the synergistic effect of the ultra-thin thickness and surface microstructure of the electrospun film, the flexible resistive pressure sensor has good resilience and fast response characteristics, and can be well applied in high-frequency and multiple-time application scenarios. Among them, the sample obtained in Example 1 has the best and most uniform nanofiber morphology while obtaining a conical microstructure, so it has good mechanical properties, such as excellent resilience and fast response. The dielectric layer in Comparative Example 1 is difficult to control its thickness due to the easy agglomeration of carbon nanotubes themselves and their scraping process, resulting in a thicker thickness of the prepared flexible sensor and a longer response time of its pressure sensor. In Comparative Example 2, the pressure sensor prepared by replacing carboxylated carbon nanotubes with carbon nanotubes has better mechanical properties, but because it is extremely easy to agglomerate, a large number of droplets will agglomerate during the spinning process, making its cyclic stability poor, affecting the spinning morphology, and unable to give the sensor relevant sensing performance. Compared with Example 1, the nanofibers of the electrospun dielectric layer prepared in Comparative Example 3 are uneven in thickness and discontinuous, and cannot provide good mechanical properties.

[0088] 3. The flexible resistive pressure sensors prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to a 1400s load cycle test (load pressure was 5KPa). Figure 9 As can be seen, the flexible resistive pressure sensors prepared in Examples 1-4 exhibit minimal performance differences from their initial performance after a 1400-second load cycle, due to the ultra-high porosity of the carboxylated carbon nanotube / thermoplastic polyurethane electrospun film layer and the inherent mechanical properties of the material. Amplifying the waveforms at the front and end of the compression phases reveals similarities between the two compression phases. However, the electrospun films of Comparative Examples 1 and 3 exhibit significant deformation under multiple cycles, thus failing to guarantee stable sensing performance.

[0089] 4. The TPU / MWCNTs-COOH spinning films with and without MXene were compared. The results are as follows: Figure 8 As shown in the figure, the addition of MXene significantly improves the sensitivity and detection range of the flexible piezoresistive sensor. This is because MXene builds a more extensive three-dimensional conductive network on the TPU fibers, significantly increasing conductivity. Furthermore, MXene forms hydrogen bonds with TPU, increasing interfacial bonding and significantly enhancing the mechanical properties of the flexible piezoresistive sensor.

[0090] 5. Comparison is made between the process flow of Example 1, Examples 2-3 and Comparative Examples 1-3 and the microscopic morphology of the flexible piezoresistive sensor prepared by selecting the conductive filler. Figure 10 We can clearly see that only when the electrospinning parameters and the selection of conductive fillers are followed in accordance with Example 1 can the self-aggregation of nanofibers occur. For example, in (a) and (b), due to the excessive content of carboxylated carbon nanotubes, the solution contains too much conductive filler, which leads to excessive aggregation into clumps during spinning, and the structure that electrospinning should have is lost. Although (c) has a micro-cone structure, it is difficult to volatilize the solution here due to the attraction of the template, forming an unreasonable micro-cone, and (d) because the conductive filler is a carbon nanotube, its spinning cannot produce a micro-cone structure under template-free conditions. And (e) due to the change in the spinning parameters, droplet agglomeration occurs, and deposition occurs at the top of the cone, resulting in poor performance and loss of the structure that the spun fiber should have.

[0091] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a flexible piezoresistive sensor by electrospinning with a micro-cone structure without a template, characterized in that: The following steps are involved: S1: Mix N,N-dimethylformamide and tetrahydrofuran, and stir until fully dispersed to obtain a mixed solvent; S2: dissolving hydrogen fluoride in a hydrochloric acid solution having a concentration of 9 mol / L to form a hydrogen fluoride-hydrochloric acid mixture; S3: Add MAX precursor to the mixture of S2, stir magnetically in a 45°C water bath for 36 hours, and wash to pH = 6 to obtain MXene nanosheets; S4: dispersing the MXene nanosheets obtained in step S3 in anhydrous ethanol to prepare a MXene / ethanol dispersion; S5: adding the carboxylated carbon nanotubes to the mixed solvent of step S1 at a mass ratio of 1:(800-1000), and performing ultrasonic treatment at a power of 12% for 10-40 minutes to obtain a carboxylated carbon nanotube dispersion; S6: adding thermoplastic polyurethane to the dispersion of step S5 at a mass ratio of 1:(8-10), stirring at 160 rpm / min at room temperature for 8 hours to form a spinning solution; S7: Inject the spinning solution from step S6 into a 10 ml syringe with a G21 needle, control the screw position to 35 mm, the voltage to 7.6 kV, and the pushing rate to 0.0030 mm / s, and electrospin for 1-2 hours at a temperature of 20° C. and a humidity of 60% RH to form a fiber film with a beaded structure; S8: placing the film from step S7 in a constant temperature and humidity chamber at 5% RH and 25° C., heating the chamber at a rate of 5° C. / min to 40° C. and maintaining the temperature for 2 hours to obtain a carboxylated carbon nanotube / thermoplastic polyurethane film having a micro-cone structure; S9: Immerse the film from step S8 in the MXene / ethanol dispersion from step S4 for 1 hour, and air-dry to obtain a carboxylated carbon nanotube / thermoplastic polyurethane / MXene composite film.

2. The method for preparing a flexible piezoresistive sensor by electrospinning with a micro-cone structure without a template according to claim 1, wherein: In step S2, 0.4 g of hydrogen fluoride is dissolved in 5 ml of 9 mol.L-1 hydrochloric acid solution to obtain a mixed dispersion of hydrogen fluoride and hydrochloric acid.

3. The method for preparing a flexible piezoresistive sensor by electrospinning with a micro-cone structure without a template as claimed in claim 1, characterized in that: In step S3, 0.003 g of MAX precursor was added to the mixed dispersion of hydrogen fluoride and hydrochloric acid, and the resulting mixture was magnetically stirred in a 45° C. water bath for 36 h and washed with deionized water until the pH of the resulting supernatant was approximately 6, thereby obtaining MXene nanosheets.

4. The method for preparing a flexible piezoresistive sensor by electrospinning with a micro-cone structure without a template as claimed in claim 1, wherein: In step S5, the mass ratio of the carboxylated carbon nanotubes to the mixed solvent is 1:1000, and the ultrasonic treatment time is 40 minutes.

5. The method for preparing a flexible piezoresistive sensor by electrospinning with a micro-cone structure without a template as claimed in claim 1, wherein: The mass ratio of the thermoplastic polyurethane to the mixed solvent in step S6 is 1:

10.

6. The method for preparing a flexible piezoresistive sensor by electrospinning with a micro-cone structure without a template according to claim 1, wherein: The electrospinning time in step S7 is 2 hours.

7. The method for preparing a flexible piezoresistive sensor by electrospinning with a micro-cone structure without a template as claimed in claim 1, wherein: In step S9, the MXene nanosheets are combined with the thermoplastic polyurethane through bonding.

Citation Information

Patent Citations

  • Piezoresistive sensor with isolation configuration

    CN222419323U